Digital Transformation for Rural Empowerment: A Web-Based Application Framework to Enhance BUMDesa Performance - Amali, Lanto Ningrayati; Tuloli, Mohamad Syafri; Katili, Muhammad Rifai (Universitas Negeri Gorontalo, 2026)
The rapid advancement of digital technology in Indonesia presents both opportunities and challenges for rural economic actors, particularly village-owned enterprises (BUMDesa). While urban MSMEs have increasingly adopted digital platforms, many BUMDesa continue to face structural and managerial barriers to digital integration. This study addresses these issues by developing the platform, a web-based application designed to enhance BUMDesa management capacity through knowledge sharing and stakeholder collaboration. Guided by the Knowledge-Based Economy and Pentahelix collaboration model, the system integrates a digital knowledge repository, user role management, web services using XML/JSON, and modules for training, article exchange, and community QA. The prototype was developed using the Waterfall method and deployed in Gorontalo and North Sulawesi. Results indicate that SIBUDE effectively facilitates real-time communication, automatic knowledge dissemination, and multi-sector cooperation. It enables BUMDesa to learn from each other, share innovations, and access a centralized, structured repository that supports continuous improvement. The study concludes that knowledge-driven digital systems can significantly empower rural enterprises by promoting transparency, innovation, and operational efficiency. Recommendations include strengthening institutional adoption, expanding data automation features, and aligning local governance with digital transformation strategies.